The WTO dispute settlement system 1995-2015: A data set and its descriptive statistics - Louise Johannesson; Petros C. Mavroidis (Research Institute of Industrial Economics (IFN), 2017)
In this paper, we provide some descriptive statistics of the first twenty years of the WTO (World Trade Organization) dispute settlement. The database used in this paper was assembled by the authors and has been publicly available (http://globalgovernanceprogramme.eui.eu/wto-case-law-project/). The statistical information that we present here is divided into three thematic units: the statutory and de facto duration of each stage of the process, paying particular attention to the eventual conclusion of litigation; the identity and participation in the process of the various institutional players, that is, not only complainants and defendants, but also third parties, as well as the WTO judges (panelists and Appellate Body members); and, finally, information regarding the subject-matter of various disputes, regarding the frequency with which claims regarding consistency of measures with the covered agreements (but also, at a more disaggregate level, e.g., specific provisions) have been raised. We call our work "descriptive statistics", because, in an effort to provide raw material that will help researchers to conduct their research as they see fit, we have consciously refrained from systematically interpreting the data that we have assembled.
Keywords: K40; 330; WTO; Dispute Settlement; Panel; Appellate Body